Intervenção Percutânea Urgente no Enfarte Agudo do Miocárdio por Lesão do Tronco Comum - Ramos, R (2008)
BACKGROUND: ST-elevation myocardial infarction (STEMI) with the culprit lesion in the left main artery is a rare cardiac emergency with a poor prognosis. OBJECTIVE: Review and prognosis evaluation of primary percutaneous coronary intervention (PCI) performed in the setting of STEMI with left main occlusion in a single high-volume center. METHODS: Of the 483 primary or rescue PCIs performed and followed in our hospital during a 24-month period (August 2004 to July 2006), we retrospectively evaluated those involving left main procedures and analyzed in-hospital mortality and major cardiac events (MACE) in a 12-month follow-up. We found nine patients, age 68 +/- 9 years, five male, seven with multivessel disease and two with isolated left main disease. Rescue PCI was performed in three patients and primary PCI in the others. RESULTS: Seven patients presented in cardiogenic shock and two were classified in Killip class II on admission. Inotropic drugs, intra-aortic balloon pump and abciximab were used in eight patients. Drug-eluting stents were used in six patients, bare-metal stents in two, and isolated balloon angioplasty in one. Five patients (55%) died in the hospital and the four discharged home (two of them aged 81 and 82 years) were still alive and free from MACE at 12-month follow-up. CONCLUSIONS: Clinical presentation of STEMI with the culprit lesion in the left main artery was very severe. During PCI, drug-eluting stents, intra-aortic balloon pump and abciximab were used in almost all patients. This entity had a high mortality rate even though primary PCI was performed. Those who survived had a good mid-term prognosis.